التغيرات البيولوجية في الحشرات ومؤشر الاحترار المناخي العالمي (اتجاهات الاستجابة والعواقب البيئية المحتملة) في ليبيا - عادل يوسف مسعود الرني (Sharwes Scientific Journal, 2025)
The research aims to shed light on the impact of global climate warming in Libya on various aspects of Insect life. the descriptive analytical approach was adopted to achieve the research objectives. graphs and statistics were also used to analyze local and global historical climate data as well as illustrative data on insect response trends towards higher temperatures in order to assess the climate warming index in Libya and its impact on the main aspects of insect life (reproduction and life cycles, organ functions, geographical distribution, biodiversity and response behavior). the results indicate that the climate warming index in Libya has become clear, which foreshadows fundamental biological changes in all aspects of insect life. the results showed that insects have unsatisfactory responses to the increasing temperature index, which portends negative environmental effects and potential serious threats to environmental systems, agricultural productivity and public health in Libya. a set of precautionary strategies have been proposed to reduce these impacts and threats to enhance environmental sustainability in Libya.